Condition analysis of the Brazilian sharpnose shark Rhizoprionodon lalandii: evidence of maternal investment for initial post-natal life - Corsso, Jessica T.; Gadig, Otto B. F. [UNESP]; Barreto, Rodrigo R. P.; Motta, Fabio S. (Wiley, 2018)
The present study analysed the condition factor (K) and the hepato-somatic index (I H ) of the Brazilian sharpnose shark Rhizoprionodon lalandii during its entire life cycle. Discontinuity of liver growth was observed after sexual maturity. High condition values were recorded in the length classes of 300–350 mm (neonates), when the livers represented about 8% of total mass, decreasing until the length classes of 400–450 and 450–500 mm in females and males, respectively. Seasonal analysis exhibited low I H values in the summer, while for K, low values were in spring, indicating greater investment for body growth during spring and for gonad maturation in summer. Such findings indicate that this small coastal shark species accumulates reserve substances in the liver that will be used during reproduction. The decline in I H values in juveniles suggests that reserves provisioned by the mother to the neonate liver can be used in the first months of life.
Keywords: condition factor; elasmobranch; hepato-somatic index; maternal investment; reproduction